The industry of forest-based products in the Philippines - Limbaro, Gindol Rey Ayala; Tor, Önder; Ateş, Saim (Artvin Coruh Universitesi Orman Fakultesi Dergisi, 2025)
This review article describes the forest products sector in the Philippines in terms of its structure, production trends, and trade. This provides an overview of wood processing plants, logs produced by species and roundwood and processed wood as well as forest-based products output. The article addresses challenges and opportunities in the sector, with emphasis on trade imbalances on exports and imports of forest-based products. Developing and optimizing the production sectors in order to contribute to the Philippine economy and penetrate to the world market is possible through identifying the current statuses and production capabilities, and the areas of improvement for processing, sustainability of business, and competitiveness.
Keywords: Forest Products Transport and Evaluation Information; Orman ürünleri; Endüstri; Üretim; Pazarlama; Ticaret; Filipinler; Orman Ürünleri Transportu ve Ölçme Bilgisi; Forest Products; Industry; Production; Marketing; Trade; Philippines